Utilization Of Family Toilet In The Allu Village Of Minasa Baji Bantimurung Districts Of Maros Regency - rahmat panyiwi (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2018)
Background: One of the efforts to improve community health status is the existence of environmental health facilities that meet health requirements, including the availability of family toilets. The absence of family latrines, or the unavailability of family toilets that meet the requirements in an area, is caused by several things such as insufficient knowledge of the residents, benefits that will be felt if they have a family toilet that meets the requirements. large funds to make eligible family latrines. Method, this type of research is